Risk Analysis for Piping Systems Subject to Corrosion Under Insulation (CUI) Using Delphi Method - Kathirasan, Yuktesvaranath (2018)
Carbon steel piping systems under thermal insulation are used widely in the world nowadays to transport mediums such as water, wastes, crude oils, gasses and chemical substances between 2 places. However, carbon steels are opened to risks from corrosion under thermal insulation (CUI) of these piping systems. Carbon steels undergo localised corrosion, which may produce pitting corrosion and thinning of wall of piping systems. In this paper, a risk identification method, which is known as the Delphi method, was used to extract opinions and ideas from targeted personnel by using a set of questionnaires. Based on the feedback from this survey, a risk analysis will be conducted in order to determine the consequence of failure and probability of failure. From the acquired consequence of failure and probability of failure, the risk rating will then be identified. In this paper, risk analysis was carried out using the Delphi method to determine the consequence of failure and probability of failure. The identified consequence of failure and probability of failure is then used to determine the risk rating if CUI in carbon steel piping systems. The risk rating of CUI in carbon steel piping systems was found to be at a medium level and the action to be taken are to implement risk control such as inspection techniques and to monitor, review and apply document control process.